Perbedaan Ekspresi Foxp3+ dan Cd8+ Tumor Infiltrating Lymphocytes Karsinoma Payudara pada Berbagai Stadium T - Anisia Indiralia; Alphania Rahniayu; Sjahjenny Mustokoweni (National Cancer Center - Dharmais Cancer Hospital, 2018)
Background: Breast carcinoma, the most common malignancy in women, are often accompanied by tumor infiltrating lymphocytes (TIL) which has controversial clinical relevance. TIL is thought to reflect the host’s immune response to malignant tumors. FOXP3, specific biomarker of Treg, is an important transcription factors that develops and functions in the maintenance of self tolerance, including inhibition of CD8+ cytotoxic T cell function. Aim: To analyze the differences and the correlation between FOXP3+ and CD8+ TIL in breast carcinoma with different T staging. Methods: An analytical observational research, performed on 44 paraffin block of breast carcinoma of various stages T (AJCC 7th ed) in anatomical pathology installation of RSUD Dr. Soetomo, used FOXP3+ and CD8+ antibodies. The immunoexpression are evaluated on stromal area, then analyzed statistically, period January 1, 2014 – December 31, 2016. Result: Showed significant differences in FOXP3+ expression between T1-T4, T2-T3, T2-T4, T3-T4. There were significant differences in CD8+ expression between T2-T3, T2-T4. There is a correlation between the expression of FOXP3+ and CD8+ in T1 and all T (p < 0.05). Conclusion: There was significant difference in FOXP3+ and CD8+ TIL of breast carcinoma with increasing T stage. There was correlation between FOXP3+ and CD8+ TIL expression of breast carcinoma at all T and T1 stage. ABSTRAKPendahuluan: Karsinoma payudara adalah keganasan terbanyak wanita dan sering didapatkan adanya tumor infiltrating lymphocytes (TIL) dengan relevansi klinis yang masih kontroversial. TIL sering dianggap mencerminkan respon imun inang terhadap tumor ganas. FOXP3, biomarker spesifik Treg, merupakan faktor transkripsi yang penting dalam perkembangan dan berfungsi dalam pemeliharaan self tolerance, termasuk penghambatan fungsi sel T sitotoksik CD8+. Metode: Penelitian observasional analitik terhadap 44 sampel blok parafin karsinoma payudara berbagai stadium T (AJCC edisi ketujuh) di instalasi Patologi Anatomi RSUD Dr. Soetomo Surabaya menggunakan antibodi FOXP3 dan CD8, dihitung pada area stroma tumor, kemudian dilakukan uji statistik periode 1 Januari 2014 – 31 Desember 2016. Hasil: Terdapat perbedaan bermakna ekspresi FOXP3+ antara T1 dan T4, T2 dan T3, T2 dan T4, T3 dan T4. Terdapat perbedaan bermakna ekspresi CD8+ antara T2 dan T3, T2 dan T4. Terdapat korelasi antara tingginya ekspresi FOXP3+ dengan tinginya ekspresi CD8+ pada T1 dan semua T (p < 0,05). Kesimpulan: Terdapat perbedaan bermakna ekspresi FOXP3+ dan CD8+ TIL karsinoma payudara dengan meningkatnya stadium T. Terdapat korelasi antara ekspresi FOXP3+ dan CD8+ TIL karsinoma payudara pada semua stadium T dan T1.